2014
DOI: 10.1680/geolett.13.00075
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical breakage mechanics and experimental assessment of stresses surrounding piles penetrating into dense silica sand

Abstract: This letter extends an earlier theoretical and numerical analysis that aimed to improve predictions for the large-displacement end-bearing capacity of piles in sand by considering the boundary conditions applying to steady penetration and the effects of grain crushing via breakage mechanics. The earlier work led to good agreement with the end-bearing capacities, soil displacements and evolution of grain size distributions observed in experiments of penetrating model piles. The purpose of the current paper is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…It remains highly challenging to undertake analyses of installation in sand that explore the generated in-situ stress fields quantitatively. However, Yang et al (2014) and Zhang et al (2014) show that an arching stress field can be expected to develop in sands around even monotonically penetrating piles. The SS and GS micro-pile experiments confirm postulate that radial stress redistribution does not contribute significantly to micro-pile ageing.…”
Section: Radial Stress Redistributionmentioning
confidence: 99%
“…It remains highly challenging to undertake analyses of installation in sand that explore the generated in-situ stress fields quantitatively. However, Yang et al (2014) and Zhang et al (2014) show that an arching stress field can be expected to develop in sands around even monotonically penetrating piles. The SS and GS micro-pile experiments confirm postulate that radial stress redistribution does not contribute significantly to micro-pile ageing.…”
Section: Radial Stress Redistributionmentioning
confidence: 99%
“…The stress and strain paths developed around the pile tip are most relevant to the pile-end bearing capacity. In some recent studies, several attempts have been made to clarify the subsoil behavior adjacent to the pile tip, such as evaluation of stress development around the pile tip (Jardine et al, 2013;Yang et al, 2014), soil crushability and the corresponding pile bearing mechanism (Kuwajima et al, 2009;Zhang et al, 2014). It is generally found that the stress around a pile is radially developed and the high stress zone is restrained near to the pile shaft.…”
Section: Introductionmentioning
confidence: 99%
“…Besides of the conventional design methods employing the model test or in-situ test, numerical methods are more and more adopted in order to reduce the economic and time costs. Among numerous approaches, the finite element method (FEM) is considered a beneficial tool in engineering design (e.g., Kouretzis et al [1], Sheng et al [2], Zhang et al [3,4], Shen and Xu [5]; Wu et al [6]), when compared with meshfree methods [7], discrete element method (DEM) [8,9]. Accordingly, a numerical platform based on FEM adopting an appropriate constitutive model would be helpful for analyzing the pile penetration considering large deformation and further estimating the pile resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this grain breakage in silica sand during pile penetration has been highlighted from a practical standpoint [3,4,[12][13][14][15][16][17][18]. Numerous studies have shown that the pile resistance in crushable sand is overestimated in comparison with that expected by a conventional simulation platform without considering grain breakage [1,3,[19][20][21]. Accordingly, the degrading effect of grain breakage on pile resistance should be considered for practical design, which poses a requirement that the constitutive model accounting for grain breakage should be employed in the numerical platform.…”
Section: Introductionmentioning
confidence: 99%